Pengaruh Perbandingan Terigu dan Tepung Ubi Jalar Cilembu (Ipomoea Batatas (L). Lam Cv. Cilembu) terhadap Karakteristik Kue Putu Ayu - Nuriya Kiromi, Ayu; Kencana Putra, I Nengah; Ekawati, I Gusti Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 1 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i01.p15, 2023)
Putu Ayu cake is a type of wet cake originated from central of java. The main ingredient for making putu ayu cake is wheat flour. Indonesia is still dependent on wheat. What needs to be done to avoid dependence on wheat flour is food diversification, one of which is using Cilembu sweet potato flour. This study aimed to determine the effect of the ratio of wheat flour and Cilembu sweet potato flour on the characteristics of the putu ayu cake and to obtain the right ratio of flour and sweet potato cilembu flour to produce the best putu ayu cake. The design used in this study was a completely randomized design (CRD) with the treatment of the ratio of wheat flour and cilembu sweet potato flour (100%:0%, 90%:10%, 80%:20%, 70%:30%, 60%: 40%, 50%:50%). Parameters observed in this study included water content, ash content, fat content, protein content, carbohydrate content, crude fiber content, swelling power and sensory assessment including color, taste, aroma and overall acceptance. The data obtained were analyzed by the analysis of variance and if there was an effect of treatment on the observed parameters, then it was continued with the Duncan Multiple Range Test (DMRT). The ratio of 60% wheat flour with 40% cilembu sweet potato flour produced the best putu ayu cake with the characteristics: water content 44.99%, ash content 0.72%, protein content 6.42%, fat content 23.02%, carbohydrates 24.83 %, crude fiber content 5.95%, swellability 22.66%, and had sensory properties with overall acceptance criteria “like”.